The Sign of the Four - Doyle, Arthur Conan, 1859-1930 (Salt Lake City, UT : Project Gutenberg, 2000)
"The Sign of the Four" by Arthur Conan Doyle is a detective novel published in 1890. When Mary Morstan seeks Sherlock Holmes's help regarding her missing father and mysterious annual gifts of pearls, the investigation leads to a buried treasure, a vengeful one-legged man, and murder. Holmes and Watson must pursue suspects through London, unraveling a decades-old conspiracy that stretches from India's colonial past to the Thames. The case tests both Holmes's deductive powers and Watson's loyalty to their intriguing client. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Sign_of_the_Four
Release date is 2000-03-01
Keywords: Holmes, Sherlock (Fictitious character) -- Fiction; Private investigators -- England -- Fiction; Detective and mystery stories